Multifunctional wound dressing with function of monitoring pH value and healing process of wound and preparation method of multifunctional wound dressing
By grafting the composite material of silanized modified bacterial nanocellulose and carbon dots with Prulan, a multifunctional wound dressing capable of monitoring wound pH and accelerated healing was developed, solving the monitoring in the prior art The complex and high cost of antibacterial dressings have achieved the effect of wound pH monitoring and healing acceleration.
Patent Information
- Application Number
- CN202411228371.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to effectively monitor wound pH and healing process, and the preparation process of antibacterial dressings is complex and costly, which limits its application in chronic wound treatment.
Using composite materials of silanized modified bacterial nanocellulose, carbon dots and Pluran, carbon dots are easily prepared by diammonium bicitric acid, loaded into silanized modified bacterial nanocellulose, and grafted with Pluran Coated to form a multifunctional wound dressing with antibacterial activity and pH response characteristics.
It realizes monitoring of wound pH and visual indication of healing process, accelerates wound healing, prevents infection and the formation of chronic wounds, and has a simple and easy preparation process and good antibacterial properties.
Smart Images

Figure CN119158067A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dressings, and particularly relates to a multifunctional wound dressing with the function of monitoring wound pH value and healing process and a preparation method thereof. Background Art
[0002] Wound variants such as sharp injuries, surgical incisions, bullet perforations, thermal and chemical injuries, puncture and bite scars, and electrical shock skin injuries are all prone to being transformed into chronic wounds that cannot heal due to internal or external factors. In addition, diseases such as diabetes can also delay wound healing and lead to chronic ulcers. Bacterial infection is another cause of chronic wound formation and the most common cause of delayed healing. The reproduction of bacteria at the site of injury can cause systemic infection and spread to other organs, tissues, bones, etc., and may even be fatal. The National Health Service (NHS) spends up to 5.5% on the treatment of chronic wounds, while the incidence of chronic wounds is about 6%. Preventing the formation of chronic wounds is crucial, especially for patients with diabetes or obesity, whose wounds are more likely to form chronic wounds; on the other hand, the development of new antibacterial dressings is also very useful and important, which can not only kill bacteria already present in the wound, but also prevent bacteria from entering and multiplying.
[0003] Carbon dots (CDs) are a new type of fluorescent nanomaterials that are widely used in different fields. Carbon dots are widely used in bioimaging (in vitro and in vivo imaging), gene and drug delivery, sensors and metal ion detection. Various natural and chemical substrates and different methods have been used to produce carbon dots. Microwave irradiation, ultrasound, laser ablation, hydrothermal and solvothermal methods are the most commonly used methods for producing CDs. The hydrothermal method is an easily accessible, controllable and simple method. The characteristics of CDs include high water solubility, nanosize (less than 10 nanometers), stability, low toxicity, biocompatibility, environmental friendliness, antibacterial activity, etc. Although some CDs have pH-responsive properties, which means that changes in pH will directly affect the optical properties of CDs, and different fluorescence intensities correspond to energy gaps, different surface states and various functional groups, the current preparation process technology is cumbersome and costly, and there are problems in further solving the performance reliability, cost-effectiveness, and large-scale preparation. Moreover, there are not many CD materials with fluorescence properties that can accurately correspond to the pH value of wound development.
[0004] Bacterial nanocellulose (BNC) is an extracellular glucan material, mainly produced by some acetic acid bacteria (such as Komagataeibacter xylinus) outside the cell. Due to its excellent properties such as high purity, ultrafine nano-scale fiber matrix, network micropores / nanopores, and non-toxicity, it has been widely used in the research and development of biomedical materials. In order to meet the requirements of various biomaterials, BNC has become the object of chemical modification, such as TEMPO and periodate oxidation, carboxymethylation, salinization, phosphorylation, etc. Silylation reaction is a well-known aminoalkylsilane grafting reaction, in which aminoalkylsilane can connect two molecules.
[0005] Pullulan is a non-toxic, highly water-soluble, non-allergenic polysaccharide, mainly produced by Aureobasidium pullulans. It has been used in tissue engineering, wound dressings, gene delivery, injectable hydrogels, oral administration and cosmetic production. Although Pul has significant effects as a biomaterial, its lack of antibacterial activity limits its application in wound healing, and when used alone as a dressing medical device, it has low mechanical strength and is difficult to operate clinically.
[0006] CN201811223273.7 discloses an intelligent antibacterial dressing for sensing and intervening treatment of infected wounds, which includes a flexible electronic device layer with a wound temperature sensing function and an ultraviolet-responsive intelligent antibacterial dressing layer with a treatment function; the intelligent dressing can predict and promptly know the occurrence of wound infection through wound temperature data, and effectively control the release of antibiotics by emitting ultraviolet light in situ on the intelligent antibacterial dressing layer, so as to treat the infected wound in time. However, the dressing contains too many materials, the preparation method is cumbersome, the operation requirements are high, and the commercial promotion is difficult, which is not suitable for large-scale promotion. The wound dressing with indicator performance developed by us does not involve antibiotics, and there is no need to worry about the abuse of antibiotics. It has a high degree of actual promotion and a high possibility of large-scale production. Summary of the invention
[0007] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a multifunctional wound dressing with the function of monitoring the pH value of the wound and the healing process and a preparation method thereof, and the multifunctional wound dressing is a BNC-based dressing with antibacterial activity, healing performance and wound pH monitoring capabilities. The dressing can accelerate wound healing, avoid infection and prevent the formation of chronic wounds.
[0008] The invention provides a multifunctional wound dressing with the function of monitoring the pH value and healing process of a wound. The dressing comprises silanized modified bacterial nanocellulose, carbon dots and pullulan Pul; wherein the silanized modified bacterial nanocellulose is a cross-linked network structure, carbon dots CDs are simply prepared by using diammonium hydrogen citrate, and then loaded into the cross-linked network of the silanized modified bacterial nanocellulose, and pullulan Pul is grafted and coated on the silanized modified bacterial nanocellulose to improve the mechanical properties deteriorated by the silanization reaction.
[0009] Preferably, the silanized modified bacterial nanocellulose is aminoalkylsilane-grafted bacterial nanocellulose membrane Ag-BNC.
[0010] The present invention provides a method for preparing a multifunctional wound dressing having the function of monitoring wound pH value and healing process, comprising:
[0011] (1) placing the bacterial nanocellulose film in a silane modifier solution and stirring to obtain silanized modified bacterial nanocellulose;
[0012] (2) immersing the silanized modified bacterial nanocellulose into a carbon dot CDs solution to obtain carbon dot loaded bacterial nanocellulose (Ag-BNC / CDs);
[0013] (3) Immersing the bacterial nanocellulose loaded with carbon dots in step (2) in a pullulan solution, and cross-linking with a cross-linking agent to obtain a multifunctional wound dressing (Ag-BNC / Pul / CDs).
[0014] Preferably, the bacterial nanocellulose membrane in step (1) is a bacterial nanocellulose membrane treated with ethanol.
[0015] The bacterial nanocellulose membrane after ethanol treatment: the BNC membrane that has never been dried is immersed in 70-75% (v / v) ethanol to replace the water in the BNC network with ethanol.
[0016] Preferably, the silane modifier in step (1) is 3-aminopropyltriethoxysilane APTES; the concentration of the silane modifier solution is 5-9% (w / v, g / mL), and the pH value is 4.0±0.3.
[0017] Preferably, in step (1), the stirring temperature is room temperature, the time is 1-3 hours, and further, the stirring temperature is 25°C.
[0018] Preferably, the concentration of the carbon dot CDs solution in step (2) is 0-2 mg / mL, and the solvent is water; and the immersion time in step (2) is 12-24 h.
[0019] Further preferably, the concentration of the carbon dot CDs solution is 1-2 mg / mL.
[0020] Preferably, the method for preparing carbon dots CDs in step (2) comprises: placing a diammonium hydrogen citrate DAHC aqueous solution in a container, covering the container with a cover (such as an aluminum foil), placing the container in an oil bath, stirring, cooling, filtering, and freeze-drying to obtain carbon dots CDs; wherein the oil bath temperature is 140° C., and the stirring time is 2-6 h; the water in the diammonium hydrogen citrate DAHC aqueous solution is double distilled water (DDW); and the concentration of the diammonium hydrogen citrate DAHC aqueous solution is 20-40 mg / mL.
[0021] Preferably, in step (3), the concentration of the pullulan solution is 10-20% (w / v, g / mL), the solvent is water; the cross-linking agent is glutaraldehyde; and the concentration of the cross-linking agent is 0.5-1% (w / v, g / mL).
[0022] Preferably, in step (3), the mixture is immersed in the pullulan solution and then stirred, wherein the stirring is performed at room temperature for 6-12 hours, and further the stirring temperature is 25°C.
[0023] The present invention provides an application of the multifunctional wound dressing having the function of monitoring the pH value and healing process of a wound in preparing a visual indicator of the wound healing process.
[0024] The present invention provides an application of the multifunctional wound dressing with the function of monitoring wound pH value and healing process in the preparation of wound healing dressing and wound pH value monitoring dressing.
[0025] The present invention uses silanized modified bacterial nanocellulose (Ag-BNC) as a substrate, loads pH-responsive carbon dots (CD) into the Ag-BNC network, and then impregnates composite pullulan (Pul). The multifunctional dressing is a visual indicator of the wound healing process and can show the progression of acute wounds to chronic wounds. It has been proven through various tests that it has the effect of inhibiting bacterial growth and accelerating wound healing.
[0026] The preparation method of the multifunctional wound dressing of the present invention is simple and easy, and the obtained dressing can simultaneously monitor the pH value of the wound to track the wound healing process, accelerate the wound healing speed and effectively resist bacteria.
[0027] Beneficial Effects
[0028] (1) The present invention develops an advanced wound dressing that not only promotes rapid wound healing and has strong antibacterial activity, but also monitors the pH of the wound to prevent the wound from becoming a chronic wound. After binding to CDs, Ag-BNC interacts with Pul to enhance the mechanical properties. At the same time, the dressing not only provides comprehensive anti-infection protection, but also helps maintain the balance between ROS generation and removal.
[0029] (2) The present invention proposes a BNC-based dressing that has antimicrobial activity, healing properties, and wound pH monitoring capabilities. The composite dressing can accelerate wound healing, avoid infection, and prevent the formation of chronic wounds, and has great potential for wound treatment of diabetic and obese patients in the future.
[0030] (3) The present invention synthesizes for the first time a pH-sensitive CD based on diammonium hydrogen citrate (DAHC) using a simple, easy and cost-effective process. The CD has a unique fluorescence corresponding to the pH of wound development, which makes it easy to observe the healing or deterioration process of the wound without opening the dressing, making it easier for doctors to quickly formulate clinical treatment plans.
[0031] (4) After the silanization reaction, the breaking stress and elongation of BNC decreased, and the mechanical properties deteriorated. Therefore, Pul was introduced and grafted onto the Ag-BNC fiber. The two synergistically improved the mechanical properties, which is beneficial for clinical operation. Compared with Ag-BNC, the composite material uniformly covered with Pul is beneficial to prevent the burst release of CDs, prolong the antioxidant and antibacterial effects and the time of pH response. Ag-BNC / Pul / CDs has faster coagulation efficiency, but better blood compatibility (lower hemolysis rate). BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Description of the figures of Examples 2 and 3, (a) TEM image of CD (scale bar is 50 nm), image of CD under sunlight (aI), image of CD under ultraviolet light with a wavelength of 365 nm (a.II); (b) size distribution of CD; (c) UV-visible spectra of DAHC and CD, excitation and emission of CD; (d) focusing spectra of CD at different excitation wavelengths; (e) focusing intensity of CD at different pH values using an excitation wavelength of 366 nm; (f) antioxidant activity of CD at different concentrations and corresponding images; (g) focusing intensity of CD composites at different concentrations; images of CD composites at different concentrations under ultraviolet light and sunlight; (h) images under sunlight (hI) and ultraviolet light (h.II) at pH values of 5-9, and original BNC (pH values are marked on the figure); (i) linear PL intensity curve of the composite made from 1.5 mg / mL CD;
[0033] Figure 2Figures for Example 4, (a) stretching curves of BNC, Ag-BNC and Ag-BNC / Pul / CDs; (b) Fourier transform infrared spectra (FTIR) of BNC, Ag-BNC and Ag-BNC / Pul / CDs; (c) XRD spectra of BNC, Ag-BNC and Ag-BNC / Pul / CDs and XPS spectra of Si 1s configuration (d), C 1s configuration (e) and N1s configuration (f);
[0034] Figure 3 Example 5 Figures, (a) antibacterial activity of BNC, Ag-BNC and Ag-BNC / Pul / CDs; (b) antibacterial mechanism of BNC, Ag-BNC and Ag-BNC / Pul / CDs against E. coli and S. aureus (scale bar is 5 μm) and color change caused by antioxidant activity and scavenging activity (c);
[0035] Figure 4 Illustrations of Example 4: (a) SEM of BNC, Ag-BNC and Ag-BNC / Pul / CDs (scale bar is 2 μm); nanofiber diameters (b), EDS spectra (c) and EDS patterns (d) of BNC, Ag-BNC and Ag-BNC / Pul / CDs.
[0036] Figure 5 The figures of Example 6 are as follows: (a) blood coagulation rate; (b) hemolysis rate; (c) scanning electron micrographs of platelets and (d) red blood cells (scale bar = 20 μm);
[0037] Figure 6 This is a figure illustration of Example 7, which shows the evaluation of the cytotoxicity and viability of BNC, Ag-BNC and Ag-BNC / Pul / CDs on L929 fibroblasts using CCK-8 (a) and fluorescent calcein AM detection reagent (b);
[0038] Figure 7 For the illustration of Example 8, BNC, Ag-BNC, Ag-BNC / Pul / CDs and Image of wounds treated with commercial dressings (a); pH response behavior of synthetic composite dressings under ultraviolet light (365nm) (b); wound healing rate (c) and daily wound closure marks (d);
[0039] Figure 8For the illustration of Example 8, on days 6 and 12, the wound tissues covered with BNC, Ag-BNC and Ag-BNC / Pul / CDs were evaluated for histomorphology using (a) H&E staining, (b) Masson staining and (c) Sirius red staining (scale bars are 200 μm and 50 μm);
[0040] Fig. 9 Schematic diagram of Ag-BNC / Pul / CDs synthesis and pH monitoring performance: (a) CDs production process in an oil bath at 140 °C for 4 h, (b) dressing fabrication, and (c) appearance of dressings at different pH values. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] Example 1
[0043] A single colony of Komagataeibacter xylinus was picked from the agar plate and transferred to a 500 mL flask containing 200 mL of Hestrin-Schramm (HS) medium. The HS medium contained 2.5%, 0.3% and 0.5% (w / v) glucose (Sinopharm Chemical Reagent Co., Ltd.), tryptone (Sinopharm Chemical Reagent Co., Ltd.) and yeast extract (Sinopharm Chemical Reagent Co., Ltd.), respectively. The pH of the medium was adjusted to 5.0 ± 0.3 with sulfuric acid (4 M) and sterilized by autoclave at 115 ° C for 30 min. The obtained bacterial culture medium was used as a seed medium, and 10% (v / v) of seeds was added to 100 mL of fresh HS medium. After static culture for 10 days, the bacterial nanocellulose produced on the surface of the liquid culture medium was harvested and rinsed continuously 8 times with 80-90 ° C double distilled water (DDW) and sodium hydroxide (1.0%). The obtained BNC membrane was stored at -4 ° C for further use.
[0044] Example 2
[0045] (1) 2 g of diammonium hydrogen citrate (DAHC, Sinopharm Chemical Reagent Co., Ltd.) was placed in a beaker and then dissolved in 100 mL of double distilled water (DDW) until a colorless solution was obtained.
[0046] (2) Cover the DAHC aqueous solution beaker with aluminum foil to prevent the solvent from evaporating quickly, and then place it in an oil bath at 140°C and stir for 4 h. When only 20 mL of the solution remains, collect the solution after natural cooling and filter it several times to remove large particles.
[0047] (3) The yellow solution (CDs) was freeze-dried and stored at -4°C for future use.
[0048] (4) The morphology and size of CDs were obtained using a transmission electron microscope (TEM, JEN-2100) and image-J software, respectively. CD images were taken under daylight and UV light (365 nm) to confirm the visual fluorescence ability of CDs. The UV-visible absorption of DAHC and CDs was performed by a UV-visible spectrophotometer (V-530, Japan) with a resolution of 1 nm.
[0049] (5) The photoluminescence (PL) spectra of CDs were recorded by a fluorescence spectrometer (FluroMax-4, France). The excitation wavelength was changed to 271, 301, 331, 361 and 391 nm, and the emission spectrum was measured in the range of 350 to 600 nm to evaluate the response of photoluminescence to the excitation wavelength. The concentrated light intensity was measured at different pH values and an excitation wavelength of 366 nm to evaluate the sensitivity of the synthesized photoCD to pH.
[0050] (6) A 1.5 mg / mL CDs solution was prepared by dissolving CDs in 2.5 mL of phosphate buffered saline (PBS) with pH values set to 5, 6, 7, 8, and 9, respectively.
[0051] (7) The antioxidant activity of the prepared CDs was measured using a DPPH free radical scavenging rate detection kit.
[0052] (8) 0.3, 0.6, 0.9, 1.2, 1.5, and 1.8 mg / mL CD were dissolved in 1 mL of nitrogen radical extraction reagent and then centrifuged at 10,000 rpm for 10 min at room temperature.
[0053] (9) The supernatant was mixed with 0.2 mL DPPH, reacted in the dark for 30 min, and then the absorbance was measured at a wavelength of 517 nm. 30 μg / mL vitamin C, ethanol, and no CD were used as positive, negative, and blank controls, respectively.
[0054]
[0055] , where A0, A1 and A2 represent the absorbance of blank, CD and negative control, respectively.
[0056] Example 3
[0057] (1) The method for preparing BNC is the same as that in Example 1.
[0058] (2) A 9% (w / v, g / mL) APTES solution (Sinopharm Chemical Reagent Co., Ltd.) was prepared and the pH was adjusted to 4.0±0.3 with acetic acid.
[0059] (3) The BNC membrane that had never been dried was immersed in 70% (v / v) ethanol (Sinopharm Chemical Reagent Co., Ltd.) to replace the water in the BNC network with ethanol.
[0060] (4) The ethanol-treated BNCs were immersed in an APTES solution and magnetically stirred at room temperature for 3 h to obtain Ag-BNCs.
[0061] (5) Ag-BNC was immersed in 0, 0.5, 1, 1.5 and 2 mg / mL CDs solutions and stirred for 12 h to screen out the lowest CDs concentration that can show ideal fluorescence. The optimal concentration was selected as 1.5 mg / mL, which is Ag-BNC / CDs.
[0062] (6) Ag-BNC / CDs with a CDs concentration of 1.5 mg / mL were immersed in a 20% (w / v, g / mL) Pul solution and stirred for 6-12 h.
[0063] (7) Glutaraldehyde was used as a cross-linking agent to promote covalent bonding and reacted at 25 °C for 12 h to obtain Ag-BNC / Pul / CDs.
[0064] (8) The PL of the composites with different CDs concentrations was quantified using image-J software.
[0065] (9) The PL values of the synthesized composite dressings were tested using PBS with pH values of 5, 6, 7, 8, and 9.
[0066] (10) The calibration curve was drawn using image-J software. In a typical measurement, the synthesized composite dressing was immersed in 20 mL of PBS with different pH values, and the Ag-BNC / Pul / CDs images at different pH values were captured. Each sample had 3 replicates.
[0067] Example 4
[0068] (1) The preparation method of BNC, Ag-BNC and Ag-BNC / Pul / CDs is the same as that in Example 3.
[0069] (2) Stress-strain curves of BNC, Ag-BNC and Ag-BNC / Pul / CDs were plotted using a universal material testing machine. The samples were cut into 2×5 cm rectangles, with 3 parallel sections per sample. The measurements were carried out at 30°C and 40% humidity with a load capacity of 100 N until fracture.
[0070] (3) A piece of undried BNC, Ag-BNC, and Ag-BNC / Pul / CDs was freeze-dried in a swollen state and characterized by Fourier transform infrared spectroscopy, XRD, XPS, scanning electron microscopy, and EDS spectra. The wavelength range of the Fourier transform infrared spectroscopy (FTIR-8400, Japan) was 400 to 4000 cm -1 , resolution 4cm -1 .
[0071] (4) XRD was recorded using a D8ADVANCE XRD scanner produced by Bruker, Germany, in the 2θ range of 10°-50°, with CuKα radiation of 8.04 keV and a wavelength of
[0072] (5) The elemental compositions of BNC, Ag-BNC, and Ag-BNC / Pul / CDs were analyzed using X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha, Waltham, Massachusetts). XPS spectra were scanned and recorded in the binding energy range of 150–600 eV and S2p range of 160–175 eV.
[0073] (6) After covering the sample surface with a very thin layer of gold, the surface morphology of the samples was observed under high vacuum conditions using a field emission scanning electron microscope (FE-SEM) (FEIQuanta FEG 250). An energy dispersive spectrometer (EDS) connected to the scanning electron microscope was used to determine the surface elemental composition of BNC, Ag-BNC, and Ag-BNC / Pul / CDs.
[0074] Example 5
[0075] (1) The preparation method of BNC, Ag-BNC and Ag-BNC / Pul / CDs is the same as that in Example 3.
[0076] (2) The antimicrobial activities of BNC, Ag-BNC, and Ag-BNC / Pul / CDs were evaluated using the direct contact method specified in ISO20743-2007.
[0077] (3) Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used as models of Gram-negative and Gram-positive bacteria, respectively. Both bacteria were cultured at 37°C until the optical density (OD) at 600 nm was 600 ) reached 0.6 to 0.7. Dilute the bacterial cells to about 10 3 -10 5 The final concentration was CFU / mL.
[0078] (4) Prepare SCDLP medium, which is a mixture of casein peptone (17 g / L), soy peptone (3 g / L), KH2PO4 (2.5 g / L), sodium chloride (5 g / L), glucose polysorbate 80 (2.5 g / L), polysorbate 80 (7 g / L), and lecithin (1 g / L).
[0079] (5) After the incubation period, the surviving bacteria on the surface of the material were washed off by vortexing with SCDLP medium, and then the bacteria were diluted and spread on agar plates and incubated for 16 h.
[0080] (6) Count the colonies formed on the agar plate and express them in CFU / mL.
[0081] (7) In order to study the antibacterial mechanism of BNC, Ag-BNC and Ag-BNC / Pul / CDs, 0.1 mL of 10 5 Bacterial cultures of CFU / mL were placed directly in contact with sterile sample pieces and incubated at 37°C for 24 h.
[0082] (8) After 24 hours, fix the bacteria on the dressing surface with 1 mL of 2.5% glutaraldehyde and culture in the dark for 4 hours.
[0083] (9) Wash the dressing three times with saline.
[0084] (10) The dressing was dehydrated with gradient ethanol (25%, 50%, 75%, 90% and 100%, v / v), and each ethanol concentration required 15 min.
[0085] (11) tert-Butanol was used instead of ethanol and the cells were incubated for another 20 min and then freeze-dried.
[0086] (12) The bacteria on the surface of each sample were observed using FE-SEM (FEIQuanta FEG 250).
[0087] (10) The antioxidant activity of the prepared BNC, Ag-BNC, and Ag-BNC / Pul / CDs was measured using a DPPH free radical scavenging rate detection kit (Shanghai Yuanye Biotechnology Co., Ltd.). BNC, Ag-BNC, and Ag-BNC / Pul / CDs were placed in a nitrogen radical extraction solution reagent and then centrifuged at 10,000 rpm for 10 min at room temperature.
[0088] (11) The supernatant was mixed with 0.2 mL DPPH and reacted in the dark for 30 min. The absorbance was then measured at a wavelength of 517 nm using a microplate reader. 30 μg / mL vitamin C, ethanol, and no CD were used as positive, negative, and blank controls, respectively.
[0089]
[0090] , where A0, A1 and A2 represent the absorbance of blank, CD and negative control, respectively.
[0091] Example 6
[0092] (1) The preparation method of BNC, Ag-BNC and Ag-BNC / Pul / CD is the same as that in Example 3.
[0093] (2) The whole blood coagulation rates of Ag-BNC / Pul / CD, BNC, and Ag-BNC were evaluated using rabbit whole blood.
[0094] (3) First, 5 mL of rabbit whole blood was activated for calcification using 0.5 mL of 0.25 M CaCl2.
[0095] (13) 0.1 mL of recalcified blood was placed in direct contact with a sterile preheated sample (circular sample with a diameter of 20 mm). After 5, 15, 25, 35, 45, and 55 min, 1 mL of double distilled water (DDW) was added to each sample. After incubation at 37°C for 10 min, the supernatant was gently collected and the absorbance was measured at a wavelength of 550 nm using a microplate reader. Each experiment was repeated three times, with three parallels for each sample. Rabbit whole blood was centrifuged at 100 g for 15 min to obtain PRP (platelet-rich plasma), and then 1 mL of PRP was added to each well, directly in contact with the sample and incubated at 37°C for 2 h.
[0096] (14) Use 1 mL of 2.5% glutaraldehyde to fix the bacteria on the dressing surface and culture in the dark for 4 h.
[0097] (15) Wash the dressing three times with saline.
[0098] (16) The dressing was dehydrated with ethanol gradient (25%, 50%, 75%, 90% and 100%, v / v), and each ethanol concentration required 15 min.
[0099] (17) tert-Butanol was used instead of ethanol and the cells were incubated for another 20 min before freeze-drying.
[0100] (18) The red blood cells on the surface of each sample were observed using FE-SEM (FEIQuanta FEG 250).
[0101] Example 7
[0102] (1) The preparation method of BNC, Ag-BNC and Ag-BNC / Pul / CDs is the same as that in Example 3.
[0103] (2) The cell counting kit-8 (CCK-8) and fluorescent calcein AM detection reagent method were used to evaluate the viability and proliferation of L929 fibroblasts in direct contact with synthetic dressings.
[0104] (3) Sterile BNC, Ag-BNC and Ag-BNC / Pul / CDs discs (1 cm in diameter) were placed in a 24-well plate.
[0105] (4) Prepare mixed culture medium: DMEM culture medium, fetal bovine serum (FBS), penicillin and streptomycin in a ratio of 9:1:0.5.
[0106] (5) Soak the dressing in the mixed culture medium.
[0107] (6) About 10 3 -10 4 cells.
[0108] (7) The culture medium was changed every day and cultured for 5 days.
[0109] (8) On days 1, 3, and 5, the dressing was rinsed three times with PBS.
[0110] (9) Add 400 μL of DMEM and CCK-8 mixture in a 9:1 ratio to each well.
[0111] (10) Incubate at 37°C and 5% humidity for 1 h.
[0112] (11) Add 100 μL of supernatant to each well of a 96-well plate.
[0113] (12) Measure the absorbance at 450 nm using an ELISA reader. Perform three replicates for each sample.
[0114] (13) For the fluorescent calcein AM detection reagent method, a fluorescent dye was added to the dressing surface on days 1, 3, and 5.
[0115] (14) The sample was incubated with the dye for 30 min.
[0116] (15) Rinse the sample three times with PBS.
[0117] (16) The cells were observed and photographed using a fluorescence microscope (OLYMPUSBX53, Japan).
[0118] Example 8
[0119] (1) The preparation method of BNC, Ag-BNC and Ag-BNC / Pul / CDs is the same as that in Example 3.
[0120] (2) Ten days before surgery, rats were randomly housed in a laboratory at a temperature of 25-35°C.
[0121] (3) The mice were fed with a standard feed containing 7% monosaccharide, 3% fat, 50% polysaccharide, 15% protein and 3.5 kcal / g net energy.
[0122] (4) The operation is performed in a sterile environment.
[0123] (5) Injection of chloral hydrate (0.4 mg / kg body weight).
[0124] (6) Shave the hair on the back of each rat and clean it with pure cotton gauze soaked in 75% (v / v) ethanol.
[0125] (7) Create a full-thickness wound (0.8 mm) on both sides of the spinal line.
[0126] (8) BNC, Ag-BNC, Ag-BNC / Pul / CDs for wounds and commercial The wound was covered with a dressing (Coloplast, USA).
[0127] (9) Change the same sterile dressing every two days.
[0128] (10) Take photos when changing the dressing until the last wound is healed to monitor the healing rate. The wound healing rate is calculated using the following formula:
[0129]
[0130] , where Day0 is the wound area on day 0, Day n is the wound area on day n.
[0131] (11) For histomorphological evaluation, rats were injected with an overdose of chloral hydrate on days 6 and 12.
[0132] (12) Wound tissues were collected and stored in paraformaldehyde (PFA) for 24 h.
[0133] (13) Tissue sections were cut and stained with H&E, Masson's, and Sirius red, and then observed and photographed under an optical microscope.
[0134] like Figure 1 As shown, morphology and size observation: The morphology of the CD was observed by TEM (a) and quantified by image-J software (b). No agglomeration was observed in the TEM image, and the main size of the CD was between 5.4±1.28nm, which was consistent with the TEM Figure 1 To Figure 1 a and b). It has been reported that the size of CD is mostly less than 10 nm, which is consistent with the findings of the present invention.
[0135] like Figure 1 As shown, absorbance and PL intensity evaluation: no fluorescence ability was observed under sunlight ( Figure 1 aI), but good fluorescence ability was observed under 365nm UV light ( Figure 1 a.II). Two absorption peaks were observed in the UV-visible spectrum of CD, corresponding to the π-π and π-n transmission of C=C and C=O, respectively. These two absorption peaks were absent in the absorption spectrum of DAHC, which confirmed the successful formation of CD ( Figure 1 c). The photoluminescence (PL) spectrum of CD shows that its excitation and emission wavelengths are 366 and 463 nm, respectively ( Figure 1 c). Different excitation wavelengths of 271, 301, 331, 361 and 391 nm were used to measure the luminescence spectra of CDs. The results clearly demonstrated that the emission peak was almost constant at 463 ± 0.8, which confirmed the uniform size of CDs ( Figure 1 d) and the results previously observed by TEM and image-J ( Figure 1 a and b).
[0136] like Figure 1 pH sensitivity evaluation and antioxidant activity: The sensitivity of the synthesized CDs to pH was confirmed by measuring the fluorescence intensity at different pH values (5, 6, 7, 8, and 9). Figure 1 As shown in Figure 5e, the fluorescence intensity of the synthesized CD decreased significantly when the pH value decreased from 9 to 5. When the PL at alkaline pH values (8 and 9) was compared with that at acidic pH values (5 and 6), a significant difference was observed, indicating that the synthesized CD has a strong potential for wound pH monitoring. In addition, the antioxidant activity of the synthesized CD at different concentrations (0.3, 0.6, 0.9, 1.2, 1.5, 1.8 mg / mL) was evaluated using a DPPH free radical scavenging assay kit. The results showed that the antioxidant activity of CD was related to its concentration. The higher the concentration, the stronger the antioxidant activity ( Figure 1 f). Figure 1 f also shows various experimental samples. The purple color disappears and turns to light yellow due to free radical scavenging. The light yellow color visually confirms the higher antioxidant activity when higher concentrations of CD are used ( Figure 1 f).
[0137] like Figure 1 As shown, the concentration of CD is optimized: Figure 1 g shows the effect of CD concentration on the light focusing intensity of the composite. The dressing was prepared using different concentrations of CD, such as 0, 0.5, 1, 1.5, and 2 mg / mL. The increase in CD concentration was directly related to the light focusing intensity of the composite until the concentration of 1.5 mg / mL, when the light focusing intensity was the highest. The light focusing intensity was lower when 2 mg / mL CD was added compared to 1.5 mg / mL.
[0138] like Figure 1 As shown, the pH sensitivity evaluation of Ag-BNC / Pul / CDs (CDs concentration is 1.5 mg / mL) composite dressing: Figure 1 h describes the appearance of the composite dressing under UV light and sunlight at different pH values. Compared with the transparent original BNC, the composite material appears pale yellow under sunlight. The pale yellow color is due to the addition of CD ( Figure 1 hI). When exposed to UV light, distinct color differences are observed at different pH values ( Figure 1 h.II). The color difference is more obvious at alkaline pH values compared to acidic pH values, which is consistent with the results of CD light intensity evaluation ( Figure 1 e). A high regression coefficient (R) with a moderately linear correlation with the PL intensity was observed. 2 =0.99), which indicates that the synthesized composite material has great application potential in pH monitoring, especially in the wound healing process ( Figure 1 i).
[0139] The tensile curve is an important feature of functional wound dressings. Due to the fragility of wound dressings, low breaking stress limits the application of dressings. The stress-strain curves of BNC, Ag-BNC and Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL) are shown in Figure 2 a. After aminoalkylsilane grafting reaction of BNC, the fracture stress and elongation of Ag-BNC decreased to 0.05MPa and 17.75mm, respectively. Compared with BNC and Ag-BNC, the fracture stress and elongation of Ag-BNC / Pul / CDs increased to 0.10MPa and 30.36mm, respectively.
[0140] Figure 2b shows the FTIR spectra of BNC, Ag-BNC and Ag-BNC / Pul / CDs (CDs concentration is 1.5 mg / mL). -1 There is a sharp peak at 2890cm, which is related to -OH stretching. This peak exists in all samples and is more obvious in Ag-BNC / Pul / CDs, indicating that Pul was successfully grafted onto BNC. -1 The other peak at corresponds to CH stretching. Both cellulose and Pul are homopolysaccharides composed of glucosyl units, the difference lies in the glycosidic bonds. In Pul, three glucosyl units are linked together by α-(1→4) glycosidic bonds, while in maltotriose, the sugar units are linked together by α-(1→6) glycosidic bonds. In cellulose, β-(1→4) glycosidic bonds link the glucose units. A peak at 1560 cm was observed in the spectrum results of Ag-BNC. -1 The peak at 1013 cm-1 observed in Ag-BNCs confirms the presence of primary amino groups (NH2) on the surface of BNCs. -1 The other peak at 913 cm represents Si-OH stretching, which disappears in Ag-BNC / Pul / CDs, which can be explained by the successful grafting of Ag-BNC with Pul. -1 and 768cm -1 The peaks at 1150 and 1135 cm represent the α-(1→4) and α-(1→6) glycosidic bonds, respectively. -1 The peaks at correspond to Si-OC and Si-O-Si stretching, respectively, which are almost in the same range as COC stretching.
[0141] Figure 2 c shows the XRD patterns of pure BNC and Ag-BNC films, and compared with Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL). According to the XRD pattern, BNC showed three peaks near 14.5°, 16.6°, and 22.6°, which were connected to the crystal lattices 101, 101-, and 002, respectively, indicating the typical cellulose I structure. Ag-BNC and Ag-BNC / Pul / CDs also had similar results, but there was no peak shift, only a decrease in peak intensity, which may be attributed to the coverage of the BNC surface by aminoalkylsilane and Pul. The XRD pattern of Ag-BNC / Pul / CDs showed a clear peak near 28(2q), corresponding to the (002) lattice of CD carbon atoms.
[0142] Figure 2d, 2e, and 2f show the XPS analysis results. Ag-BNC and Ag-BNC / Pul / CDs (CDs concentration is 1.5 mg / mL) show a peak near 398 eV, representing the binding energy of Si 1s, indicating the presence of aminoalkylsilane. Due to the covering effect of Pul, the aminoalkylsilane in Ag-BNC is sharper than that in Ag-BNC / Pul / CDs ( Figure 2 d). Figure 2 e shows two peaks at 285 eV and 283 eV, which are attributed to the binding energy of C1s. Figure 2 f shows the binding energy of the N1s configuration, indicating a peak at 101 eV, which is sharper in the case of Ag-BNC, verifying the successful grafting of aminoalkylsilane, while in Ag-BNC / Pul / CDs, this peak is reduced due to the covering effect of Pul.
[0143] Figure 3 The results of the evaluation of the antibacterial activity of Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL) were compared with BNC and Ag-BNC. After 24 hours of direct contact between the bacterial suspension and the sample, Ag-BNC showed higher antibacterial activity, which was due to the grafting of aminoalkylsilane on the surface of BNC, which had antibacterial activity against both bacterial strains ( Figure 3 a). Compared with BNC, the antibacterial activity of Ag-BNC / Pul / CDs was significantly lower than that of Ag-BNC. In the case of Ag-BNC / Pul / CDs, a thin layer of Pul covered the surface of Ag-BNC, which reduced the antibacterial activity of Ag-BNC / Pul / CDs. A greater number of E. coli and S. aureus were observed on the surface of BNC compared with Ag-BNC and Ag-BNC / Pul / CDs, which was consistent with the results of the direct contact method ( Figure 3 b) The antibacterial mechanism of Ag-BNC may be due to the destruction of cell wall integrity, which reduces the number of bacteria on the Ag-BNC surface and avoids bacterial reproduction. Figure 3 As shown in Figure c, the antioxidant activities of BNC, Ag-BNC, and Ag-BNC / Pul / CDs were 5%, 6.2%, and 62.4%, respectively. Various experimental sample graphs are also provided to observe the color changes caused by free radical scavenging activity. When free radical scavenging occurs, the typical purple color disappears, which indicates antioxidant activity. It is obvious that Ag-BNC / Pul / CDs has significant antioxidant activity. The reason for the slight color change after DPPH came into contact with BNC and Ag-BNC may be that the DPPH solution was diluted in the water content of BNC and Ag-BNC.
[0144] Figure 4a and 4b represent the SEM images of nanofibers of BNC, Ag-BNC, and Ag-BNC / Pul / CDs (CDs concentration is 1.5 mg / mL) and the size distribution of fiber diameter. Typical BNC nanofibers with an average diameter of 33.5±15 nm can be observed from the SEM image of the original BNC membrane. Due to the grafting of aminoalkylsilane on the surface of BNC, the fiber diameter in Ag-BNC increased, and the average diameter reached 65±25 nm. The average diameter of the nanofibers in Ag-BNC / Pul / CDs is 93±29 nm, which is the largest, proving that Pul is successfully attached to Ag-BNC. EDS spectrum results ( Figure 4 c element distribution and Figure 4 d element distribution fluorescence diagram) showed that the carbon content in BNC, Ag-BNC, Ag-BNC / Pul / CDs (CDs concentration was 1.5 mg / mL) was 55.9%, 58.1%, and 61.2%, respectively. Si and N were only observed in Ag-BNC and Ag-BNC / Pul / CDs, with Si being 6.3% and 1.2%, and N being 7.1% and 2.1%, respectively. Aminoalkylsilane contains both Si and N and is covered by a thin layer of Pul in Ag-BNC / Pul / CDs. The contents of O and C in Ag-BNC / Pul / CDs were high (61.2% and 34.5%, respectively), indicating that Pul was attached to Ag-BNC and that Pul was evenly distributed after grafting. Composite materials uniformly covered with Pul are beneficial to prevent the burst release of CDs and prolong the antioxidant and antibacterial efficacy and the aging of pH response.
[0145] Figure 5 a The effect of synthetic dressings on blood coagulation rate was evaluated. Compared with BNC and Ag-BNC, Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL) showed the best coagulation rate at each time point within 55 min. The coagulation rate was faster within the first 35 min when the blood was in direct contact with the sample; after 35 min, the coagulation rate of all samples slowed down. Figure 5The results of the evaluation of the hemolysis rate are also shown in b. The hemolysis rate is a parameter that indicates the leakage of hemoglobin from damaged red blood cells into the plasma. Values below 5% can be used as safe and functional wound dressings. The hemolysis rate of Ag-BNC / Pul / CDs was close to that of the original BNC, which was 0.35%. The highest hemolysis rate (0.96%) was observed when blood was in direct contact with Ag-BNC, which is below the limit for functional dressings. The hemolysis rate values of Ag-BNC and Ag-BNC / Pul / CDs both indicate that they are non-hemolytic materials according to the ASTM F756 standard (<2%) (ASTM, 2016). Morphological observation of red blood cells using SEM confirmed that a small number of red blood cells were ruptured or had morphological changes ( Figure 5 c and 5d), which indicates that Ag-BNC / Pul / CDs are biocompatible with erythrocytes. Erythrocytes adhere to the Ag-BNC surface, which is most likely due to their electrostatic interaction with aminoalkylsilane. However, erythrocyte aggregation was also observed on the surfaces of BNC and Ag-BNC / Pul / CDs. This result indicates that Ag-BNC / Pul / CDs have faster coagulation efficiency but better blood compatibility (lower hemolysis rate) compared with Ag-BNC.
[0146] L929 fibroblasts were cultured on the surfaces of BNC, Ag-BNC, and Ag-BNC / Pul / CDs (CDs concentration was 1.5 mg / mL) to evaluate the cell viability and cytotoxicity of the dressings. Figure 6 As shown in Figures 6a and 6b, the viability and proliferation of fibroblasts increased over time in all samples. However, the proliferation rate of fibroblasts was much higher in the presence of Ag-BNC / Pul / CDs, followed by BNCs and then Ag-BNCs. Fluorescent calcein AM detection also confirmed the results of CCK-8 and showed that the growth and proliferation rates were higher in the presence of Ag-BNC / Pul / CDs compared with BNCs and Ag-BNCs.
[0147] Figure 7 BNC, Ag-BNC, Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL) and commercial Evaluation of wound healing ability in vivo. Figure 7 a, c, d show the intuitive photos, healing rates and representative images of the wounds on days 0, 4, 8 and 12. After 4 days, the wounds covered by Ag-BNC / Pul / CDs were significantly reduced, followed by BNC and Ag-BNC. The wounds covered with Ag-BNC / Pul / CDs healed the slowest, which may be due to secondary injury caused by the removal of the dressing. On day 8, the wounds covered with Ag-BNC / Pul / CDs showed the fastest healing rate among all dressings. The wounds covered with Ag-BNC / Pul / CDs were completely healed on day 12, while the wounds covered with BNC, Ag-BNC, The wounds healed on the 14th, 18th and 20th days respectively. Figure 7 b shows the pH-responsive behavior of Ag-BNC / Pul / CDs when they were in direct contact with the wound. After 4 days, the pH-responsive dressing showed fluorescence, and the fluorescence intensity increased on the 8th day, indicating an increase in the wound pH. However, as the wound healed, the fluorescence intensity decreased on the 12th day. This trend continued until pH = 8 to avoid bacterial infection, and then after epithelialization, the pH value slowly decreased to normal values. The above trend was clearly reflected on the Ag-BNC / Pul / CDs and was successfully detected under UV light ( Figure 7 b), it was confirmed that Ag-BNC / Pul / CDs can be used as a real-time pH monitoring composite material for wound healing process.
[0148] Figure 8 Wound tissues covered with BNC, Ag-BNC, and Ag-BNC / Pul / CDs (CDs concentration of 1.5 mg / mL) were harvested on days 6 and 12, and the sections obtained were stained with H&E, Masson, and Sirius red. After 6 days, the accumulation of neutrophils and macrophages in wounds covered with BNC, Ag-BNC, and Ag-BNC / Pul / CDs was different. Compared with BNC and Ag-BNC, wounds covered with Ag-BNC / Pul / CDs had a higher degree of inflammation caused by the accumulation of neutrophils and macrophages ( Figure 8 a). In addition, the highest vascularization rate was observed in wounds covered with Ag-BNC / Pul / CDs on day 6. Granulation was evident in all tissues evaluated. After 12 days of treatment with the dressings, inflammation was effectively reduced in all wounds, but significantly reduced in wounds treated with Ag-BNC / Pul / CDs. Wounds dressed with Ag-BNC / Pul / CDs re-epithelialized faster. In addition, a large number of skin appendages, including sebaceous glands, hair follicles, and keratinized layers, were observed in wounds treated with Ag-BNC / Pul / CDs ( Figure 8 a). In addition, in the wounds covered with Ag-BNC / Pul / CDs, the number of cells responsible for collagen synthesis was higher, followed by BNC and Ag-BNC ( Figure 8b). On day 12, the collagen fiber density of wounds covered by Ag-BNC / Pul / CDs was significantly higher than that of wounds covered by BNC and Ag-BNC. The results clearly showed that Ag-BNC / Pul / CDs had a positive effect on full-thickness wound healing.
[0149] To monitor the quality of wound healing, Sirius red staining was used to detect collagen deposition in the healing tissue on days 6 and 12. Green and yellow-green represent type III collagen fibers, while type I collagen represents orange and red fibers. Sparse, delicate birefringent green and yellow-green reticular collagen fibers with a large number of gaps between the fibers were observed in both BNC- and Ag-BNC-covered wounds. Compared with the other groups, the wounds covered with Ag-BNC / Pul / CDs not only showed abundant collagen formation, but also a more mature and organized fiber structure. In addition, this group also replaced type III collagen with type I collagen in advance within 6 days. On day 12, green and yellow-green collagen fibers were scarce and quite fragile in the wounds covered with BNC and Ag-BNC, especially on the wound surface ( Figure 8 c). In the wound covered by Ag-BNC / Pul / CDs, the fibers were more obvious and the reticular arrangement was more obvious, while in addition to the yellow-green fibers parallel to the wound surface, some fine orange fibers were also deposited.
[0150] Comparative Example 1
[0151] A method for preparing a calcium alginate-based gel material with a fluorescent reversible effect. First, a calcium alginate gel with a fluorescent effect is prepared, and the gel is immersed in a solution containing copper ions to obtain a calcium alginate-based gel material with fluorescence quenching; then the copper ions in the gel material are released to obtain a calcium alginate-based gel material with a fluorescent effect. The antibacterial effect of the dressing is intelligently monitored by a fluorescent reversible response. The material is cumbersome to prepare and has high requirements for the preparation process. The release of copper ions and calcium ions is used to achieve antibacterial effect, but its antibacterial and biocompatibility are easily affected, and the actual effect of the product is difficult to be stably exerted.
[0152] The Ag-BNC / Pul / CDs dressing developed by the present invention is not only simple to prepare and highly practical, but also does not involve metal ions and has stable antibacterial ability and good biocompatibility.
Claims
1. A multifunctional wound dressing with the function of monitoring wound pH and healing process, characterized in that: The dressing comprises silanized modified bacterial nanocellulose, carbon dots and pullulan Pul; wherein the silanized modified bacterial nanocellulose is a cross-linked network structure, the carbon dots CDs are loaded into the cross-linked network of the silanized modified bacterial nanocellulose, and the pullulan Pul is grafted and coated on the silanized modified bacterial nanocellulose.
2. The multifunctional wound dressing according to claim 1 is characterized in that: The silanized modified bacterial nanocellulose is a bacterial nanocellulose membrane Ag-BNC grafted with aminoalkylsilane.
3. A method for preparing a multifunctional wound dressing having the function of monitoring wound pH value and healing process, comprising: (1) placing the bacterial nanocellulose film in a silane modifier solution and stirring to obtain silanized modified bacterial nanocellulose; (2) immersing the silanized modified bacterial nanocellulose in a carbon dot CDs solution to obtain carbon dot-loaded bacterial nanocellulose; (3) Immersing the bacterial nanocellulose loaded with carbon dots in step (2) in a pullulan solution, and cross-linking with a cross-linking agent to obtain a multifunctional wound dressing.
4. The preparation method according to claim 3, characterized in that: The bacterial nanocellulose membrane in step (1) is a bacterial nanocellulose membrane treated with ethanol; the silane modifier is 3-aminopropyltriethoxysilane APTES; the concentration of the silane modifier solution is 5-9% (w / v) and the pH value is 4.0±0.3; the stirring temperature in step (1) is room temperature and the stirring time is 1-3h.
5. The preparation method according to claim 3, characterized in that: The concentration of the carbon dot CDs solution in step (2) is 0-2 mg / mL, and the solvent is water; the immersion time in step (2) is 12-24 h.
6. The preparation method according to claim 3, characterized in that: The method for preparing carbon dots CDs in step (2) comprises: placing a diammonium hydrogen citrate DAHC aqueous solution in a container, covering the container, placing the container in an oil bath, stirring, cooling, filtering, and freeze-drying to obtain carbon dots CDs.
7. The preparation method according to claim 3, characterized in that: In the step (3), the concentration of the pullulan solution is 10-20% (w / v), the solvent is water; the cross-linking agent is glutaraldehyde; and the concentration of the cross-linking agent is 0.5-1% (w / v).
8. The preparation method according to claim 3, characterized in that: In the step (3), the mixture is immersed in the pullulan solution and stirred, wherein the stirring is performed at room temperature for 6-12 hours.
9. Use of the multifunctional wound dressing according to claim 1 in preparing a visual indicator of a wound healing process.
10. Use of the multifunctional wound dressing according to claim 1 in preparing a wound healing dressing and a wound pH monitoring dressing.
